PERILAKU KONSUMEN DAGING AYAM BROILER DI PASAR TRADISIONAL DAN MODERN - Franky N.S Oroh; Stevy P Pangemanan (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
The purpose of this study was are to describe consumer behavior in buying broiler meat at the traditional and Modern Market. This research was conducted September-Oktober in Sorong City, West Papua. The sampling method used accidental sampling, and used descriptive data analysis. Variables namely Quality, Location, Price, and product information. The results of the study were obtained. First, broiler meat distribution channels at Saga supermarkets, namely from breeders to retailers and to consumers. Supermarker Saga as a Retail Merchant. The behavior of broiler meat consumers based on the quality of the meat in the Warmon market was 64%, because consumers prefer the freshness of traditional market meat. Based on location, consumers prefer Saga supermarkets as much as 74% because of complete facilities and convenience. Based on the price of broiler meat, the percentage of supermarket saga is 66% because this place sells meat according to the wishes of consumers in the form of cuts of meat at the right price. Based on information from Saga supermarkets, there were 78% due to more information on products to consumers through sosial media.